2020
DOI: 10.3390/plants10010036
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Effects of Plant Essential Oils: A Systematic Review and Structure-Activity Relationship Based on Chemometric Analyses

Abstract: Herbicides are natural or synthetic chemicals used to control unwanted plants (weeds). To avoid the harmful effects of synthetic herbicides, considerable effort has been devoted to finding alternative products derived from natural sources. Essential oils (EOs) from aromatic plants are auspicious source of bioherbicides. This review discusses phytotoxic EOs and their chemical compositions as reported from 1972 to 2020. Using chemometric analysis, we attempt to build a structure-activity relationship between phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 56 publications
4
60
2
1
Order By: Relevance
“…The E. aellenii showed a positive correlation with E. hirta (r=0.70), while E. caracasana showed a strong correlation with E. cotinifolia . The observed correlations among different Euphorbia species could be attributed firstly to the genetic variation and maybe ascribed also to the variation in the climatic and environmental variables [2,3] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The E. aellenii showed a positive correlation with E. hirta (r=0.70), while E. caracasana showed a strong correlation with E. cotinifolia . The observed correlations among different Euphorbia species could be attributed firstly to the genetic variation and maybe ascribed also to the variation in the climatic and environmental variables [2,3] …”
Section: Resultsmentioning
confidence: 99%
“…Secondary metabolites of plants have gained great interest, due to their significant role in the treatment of various diseases with fewer side effects [1] . Essential oils have been reported to exhibit different biological activities such as sedative, anxiolytic, stress reliever, anti‐depressant, antimicrobial, anti‐inflammatory, and anticancer activities besides their nutritional and cosmetic applications [2] . Moreover, EOs have a great contribution in the agrochemical field due to their allelopathic effects on several harmful weeds which may stop and/or decrease the use of synthetic pesticides in the near future [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for the selection of those compounds were the amount obtained and whether information was available regarding their phytotoxicity in the literature. Monoterpenes, such as 1 and 3 , were already described as phytotoxic compounds that can be found in the essential oils of several species [ 33 ]. Regarding the new compound 4 , only 2.3 mg had been obtained, which was not enough to carry out the bioassay.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that monoterpenes, citronellal, linalool, and cineole prolong the weed germination time and also reduce their development, e.g., Cassia occidentalis . Citronellal and linalool at 110 M and 55 M concentrations, respectively, completely stifled weed germination [ 112 ]. A related study on Raphanus sativus L. and Lepidium sativum , geraniol, carvone, borneol, and citronellol conferred significant inhibitory effects on seed sprouting and radical elongation of the two species of plants [ 113 , 114 ].…”
Section: Role Of Terpenes In Plant Protectionmentioning
confidence: 99%